Beyond The Numbers: How Accounting Information Shapes The Information Content Of Prices – A Systematic Literature Review - Sandy, Khairum Nadila; Fitriani, Fitriani; Darmawati, Darmawati; Syarifuddin, Syarifuddin (Lembaga Riset Ilmiah, 2025)
This study aims to systematically review the relationship between accounting information and price informativeness in the capital market. Using a Systematic Literature Review (SLR) approach to 39 scientific articles for the period 2015–2025, this study identifies how accounting information affects the mechanism of stock price formation and market efficiency. The results of the study show that accounting information has significant value relevance in explaining stock price variations. Profit and cash flow serve as signals of economic performance, while book value and reporting quality reinforce investor confidence in a company's fundamental value. In addition, the high level of disclosure has been shown to reduce information asymmetry and increase market transparency. However, the strength of these relationships is influenced by institutional contexts such as regulation, investor protection, and governance effectiveness. The findings also confirm that digital reporting innovations through XBRL, big data analytics, and machine learning accelerate the transmission of accounting information and strengthen pricing efficiency. Overall, this study confirms that accounting information is not just a historical reporting tool, but a strategic infrastructure in shaping the efficiency and credibility of the modern capital market.